Chapter 4: Stories of Networks of Help During the Holocaust - Baruch, Adele (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2019)
Stories of helping during the Holocaust offer opportunities to reflect on the choice to act in the face of great suffering and danger. Those who listened to these stories of helping had the chance to explore the circumstances, internal and external resources, and the relationships that made the choice to act possible. Stories of helping from different geographical and political contexts were shared by participants. Some of these contexts, such as Zakynthos in Greece, and all of Denmark, had leadership and a social and political history that helped to create conditions for interactive networks of helping. Some contexts, such as Central Greece, offered more isolated, individual opportunities to help. In some cases, narratives carried through resistance networks sustained and supported helping activities. Those who heard stories of courageous acts of helping carried a sense of pride and identification with the efforts to help. Individuals who heard stories of help and resistance after the war grappled with questions about how they might react in similar circumstances.